Analyzing Sports Injuries of Kabaddi Players: A Systematic Review - Dicky Hendrawan; Alan Alfiansyah Putra Karo Karo; Dewi Maya Sari; Liliana Puspa Sari (OVS LLC, 2024)
Objective. This study aimed at analyzing sports injuries of kabaddi players through a systematic review. Materials and Methods. This review study adhered to the PRISMA guidelines for systematic reviews and meta-analyses.The study must have been published within the previous five years, from 2020 to 2024. The search procedure was conducted using the keywords (1) kabaddi, and (2) injuries. The Scopus search engine was used in this study. Results. The search results in the database produced 104 articles that were adjusted to the criteria into 5 articles. Four articles summarized knee injury, one article focused on ACL tear injury, one article summarized the prevalence of traumatic orofacial injuries and traumatic episodes, two articles addressed ankle injuries and one article described and summarized shoulder injury. Conclusions. The analysis of sports injuries in kabaddi players using a systematic review's findings leads to the conclusion that common injuries among kabaddi players are ACL tear injuries, knee injuries, prevalence of traumatic orofacial injuries, widespread presence of traumatic episodes, ankle injuries and shoulder injuries.